Smart kitchen : recipe recommendation system - Yap, Lee Leng (2010)
Today want to eat or cook what meals? This is a common question that everyone asking, especially the housewife. Many people busy on work, some of them no time to think the meal that they want prepare to their family at night. Children are very changeable, not easy to think the meal prepare to them every day. Therefore, this project is carried out to build a prototype for recipe recommendation. It gives recommender or suggest recipe to the user based on their preference or the ingredient that available. The system is a web based system, it develop for those who are in rush. The Linear Model of Expert System Development Life Cycle is implemented in the system development. The rule is design based on the recipe that collected from web sites and book.